Resting state electroencephalography microstates in autism spectrum disorder: A mini-review - Das, Sushmit; Zomorrodi, Reza; Enticott, Peter G.; Kirkovski, Melissa; Blumberger, Daniel M.; Rajji, Tarek K.; Desarkar, Pushpal (Frontiers in Psychiatry, 2022)
Atypical spatial organization and temporal characteristics, found via resting state electroencephalography (EEG) microstate analysis, have been associated with psychiatric disorders but these temporal and spatial parameters are less known in autism spectrum disorder (ASD). EEG microstates reflect a short time period of stable scalp potential topography. These canonical microstates (i.e., A, B, C, and D) and more are identified by their unique topographic map, mean duration, fraction of time covered, frequency of occurrence and global explained variance percentage; a measure of how well topographical maps represent EEG data. We reviewed the current literature for resting state microstate analysis in ASD and identified 8 publications. This current review indicates there is significant alterations in microstate parameters in ASD populations as compared to neurotypical (NT) populations. Microstate parameters were also found to change in relation to specific cognitive processes. However, as microstate parameters are found to be changed by cognitive states, the differently acquired data (e.g., eyes closed or open resting state EEG are likely to produce disparate results. We also review the current understanding of EEG sources of microstates and the underlying brain networks.